CONSTRUCTED WETLAND PADA AIR LIMBAH DOMESTIK UNTUK KONSERVASI AIR TANAH TINJAUAN SISTEMIK DAN APLIKASI TEKNOLOGI - , ACHMAD BAQI.ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Rapid population growth in Indonesia especially in big cities, has prompted an increased need for housing, thus increasing the amount of domestic wastewater. The increasing amount of domestic wastewater that is not offset by an increase in receiving water bodies from both aspects of capacity and quality, causing the amount of wastewater that enters the receiving water body exceeds the capacity. To anticipate the potential impact, waste minimization efforts are needed through a variety of alternative waste treatment technologies that effectively and efficiently, one alternative is to use an artificial wetland system (constructed wetlands). This study aims to design and knowing of the utilization efficiency to BOD, TSS and pH and systemic review and application technologies trough Constructed Wetlands combined with irish SP plant in domestic wastewater treatment system from the economic and social aspects. Constructed Wetland installing in series with a unit of Septic Tank and Anaerobic Filter. Unit Constructed Wetland in this study serves as a secondary treatment. The wastewater flowed into the septic tank (sedimentation tanks) that serves as a pre treatment and then processed in anaerobic filter tub as the primary treatment. In this study sampling conducted at the inlet of septic tank, inlet of the wetland units, and the last sampling is at the outlet of wetland unit. Sampling was done since November 4 th 2010 to January 3 rd 2011 with duration within 2 days. For the purposes of scale-up the units constructed wetland values obtained reaction rate constant of first-order area (kA) for BOD is 0.156 m / day, TSS valued at 0.173 m / day, TN valued at 0.176 m / day, and the TP value of 0.277 m / day. On units constructed wetland values obtained volumetric reaction rate constant of first order (kV) for BOD value of 0.893% / day, worth 0.991 TSS / day, TN valued at 1.006 / day, and TP valued at 1.584 / day. Efficiency units in the anaerobic filter pollutants degrade BOD to 56.87%, and 33.07% TSS removal. The efficiency of constructed wetland units in degrading BOD is 69.12%, and 71.4% TSS removal. Total efficiency of wastewater treatment systems with anaerobic units and constructed wetland filters mounted in series BOD removal was 86.64%, and 80.83% TSS removal.